Beyond Dichotomies: Re-Assessing Gender History and Women's History in Canada - Sangster, Joan (Left History: An Interdisciplinary Journal of Historical Inquiry and Debate, 1995)
Canadian women's history, though relatively new in the history of the profession, is now considered by some to be passé, past its prime, out of touch with the realities of the postmodern world of the 1990s. In fact, there is also a new interpretation of the historical evolution of Canadian women's history emerging, which situates women's history in the one dimensional past, gender history in the three dimensional future. ...[W]e need to re-examine the Canadian women's history which was actually written over the last twenty years as well as the current direction of gender history, then assess the theoretical and political underpinnings of both. We may actually find more overlapping continuities, similarities and problems. –Introduction than stark contrasts and oppositions.